2015
DOI: 10.5489/cuaj.2735
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser transurethral incision of the prostate: Can prostate size predict the long-term outcome?

Abstract: Introduction:We determine the impact of prostate size on the long-term outcome of holmium laser transurethral incision of the prostate (Ho-TUIP) for bladder outlet obstruction (BOO) secondary to benign prostate enlargement (BPE). Methods: A retrospective review of prospectively collected data was performed for patients undergoing Ho-TUIP by a single surgeon for patients presenting with lower urinary tract symptoms (LUTS) secondary to BOO. Patients were stratified into 2 groups: Group 1 included patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…7,8 In the current retrospective study of 80 patients, Elkoushy and colleagues demonstrate a durability of benefits with long-term 5-year follow-up in prostate volumes <30 cc. 9 Interestingly, re-operated patients (11%) after Ho-TUIP had significantly larger prostate volume (36.8 ± 8.9 vs. 27.6 ± 5.1 cc, p < 0.001). Furthermore, the authors showed in a multivariate regression model that only prostate size independently predicted re-operation (adjusted odds ratio 95% confidence interval 7.12 [2.92-9.14], p = 0.01).…”
Section: S Ince Its Initial Description In 1969 Bymentioning
confidence: 87%
“…7,8 In the current retrospective study of 80 patients, Elkoushy and colleagues demonstrate a durability of benefits with long-term 5-year follow-up in prostate volumes <30 cc. 9 Interestingly, re-operated patients (11%) after Ho-TUIP had significantly larger prostate volume (36.8 ± 8.9 vs. 27.6 ± 5.1 cc, p < 0.001). Furthermore, the authors showed in a multivariate regression model that only prostate size independently predicted re-operation (adjusted odds ratio 95% confidence interval 7.12 [2.92-9.14], p = 0.01).…”
Section: S Ince Its Initial Description In 1969 Bymentioning
confidence: 87%
“…25 Short-and long-term functional outcomes of these different procedures have been previously published, including 3 randomized controlled trials comparing the 3 generations of the 532-nm laser with holmium laser ablation and enucleation. [26][27][28][29][30][31][32] In our current study, all 3 successive groups were comparable regarding long-term adverse events and reoperation rates. However, there was a progressive decrease in the incidence of urethral stricture over time.…”
mentioning
confidence: 79%
“…The vaporization of prostatic tissue induced by the use of holmium laser could be however the main culprit for the high rate of retrograde ejaculation, which is reported to be around 25-27% [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Its main limitation is however a relatively high rate of retrograde ejaculation, which may affect up to 27% of younger men undergoing this procedure [5,6]. As showed in same epidemiological studies, absence of ejaculation affects sexual activity and global quality of life (QoL) [7,8].…”
mentioning
confidence: 99%